Fostering Spirituality for the Secondary Level Students Through Language Teaching - Paunanthie, A.; Tholappan, A. (Scribe & Scroll Publishing LLC, United Kingdom, 2025)
In particular, this chapter reflects on how language teaching in high school can be a powerful tool for developing students' spirituality. This concept is integral to understanding the holistic human being. It is important to note and clarify that an understanding of spirituality in education is not about religion. However, its focus depends on meaning, purpose, and a sense of relatedness as well as interconnectedness in the world. Language is described as the agent of spiritual exploration, thought, intimacy, and moral development via reflection and dialogue. Four compatible pedagogies of self-reflectiveness, dialogue about values and meaning, connectedness and empathy, and generative creativity are suggested for classroom application. There are certainly drawbacks, especially in terms of blurring the line between spirituality and religion, but in these practices, the role of the teacher becomes that of the facilitator or nurturer of development. This chapter concludes that it is precisely the force of language that nurtures spiritual identity and provides students with the social and emotional fortitude necessary for mature and responsible human development.
Keywords: Spirituality Development; Language Teaching; Education; Pedagogy; Transformative Learning; Holistic Education